The manufacturer’s perspective on supply chain flexibility and customer satisfaction - Manders, Jorieke H.M.; Caniëls, Marjolein C.J.; Ghijsen, Paul W.Th.; Mulder, Joris (Sustainability Letters, 2023)
Studies have shown how isolated flexibility dimensions are related to customer satisfaction. Little is known about what manufacturers perceive as important for customers. Yet, manufacturers’ perceptions govern their actions and are likely to determine the relative investments in each flexibility dimension. The purpose of this study is to empirically investigate supply chain flexibility from the manufacturer’s perceptive to see which flexibilities will increase the level of customer satisfaction when all flexibility dimensions are taken into account at the same time. We gathered survey data from managers in Dutch manufacturing companies. Results from structural equation modelling imply that in the eyes of the manufacturer, only logistics and spanning flexibility are perceived to have a significant positive impact on customer satisfaction. Using Bayesian model selection, we find that manufacturing managers prioritize spanning, then logistics, then manufacturing and then product development flexibility. Hence, the importance of product development flexibility and manufacturing flexibility, though highly valued by customers, are currently less acknowledged by manufacturers. With our study, we create awareness for the manufacturer’s perspective on supply chain flexibility, which tend to focus on the service to the customer. Our study identifies the directions in which a further improvement of customer satisfaction can be achieved.